To the Question of the Localization of Basoropeda in the Ligth of the Conquests of Artashes I from Medes - Kobzar, Ruslan; Tsatryan , Vigen (History and Culture, 2021)
The article points our the error of Strabo in the description of the Araks River, which was the border beween Greater Armenia and Atropatena. Based on this facts, autors show that the are two Araks River in the Armenian Highlands. Unaware of this, Strabo combined the source of one Araks (Gedar-su, Arag), which originates in the slopes of Mount Zarasp and flows into Lake Urmia, which the middle cource of the other Araks, originated from Mount Byurakn (Bingel-dag) and flows into the Caspian Sea. As a result of this, there is nonexistent turn of Araks (Arag, Gedar-su) to the west and a current to the north, from the sity of Azara (old Armavir) arose. In view of this, was proposed a new etimological localization of Basoropeda region concured by Artashes I from the Medes. Relying on Assyrian sources on the location of the land of Gizilbunda the autors suggest identifying Gizilbunda-Atropatene-Basoropeda countries, taking into account the possibility of change of the historical boundaries.